MAPATON 2023: implementing a tool for the analysis of forest fire zones in Arequipa - Natalia I. Vargas-Cuentas; Meyluz Paico-Campos; Abel Cahuana; Elber E. Canto-Vivanco; Tania Valencia; Sebastian Ramos-Cosi; Peter Villena; Avid Roman-Gonzalez (Institute of Advanced Engineering and Science, 2024)
The